Managing iatrogenic tracheal injury during esophagectomy - Pegu, Niju; Purkayastha, Joydeep; Talukdar, Abhijit; Borthakur, Bibhuti; Kalita, Dipjyoti; Das, Gaurav; Bannoth, Srinivas; Yadav, Jitin; Kalita, Dwipen; Singh, Pritesh (International Surgery Journal, 2019)
Iatrogenic tracheal injuries are uncommon, but potentially lethal and associated with significant morbidity. During esophagectomy the proximity of the trachea to esophagus makes it vulnerable to injury. The reported incidence of tracheal injury during esophagectomy ranges between 1-5%. Various methods for repairing tracheal injuries have been described in the literature. Most preferred mode of repair described is the reinforcement of the primary repair with flap cover. Most common autologous flaps used are pericardium, pleura, extra thoracic muscle flaps and intercostal muscle flaps. Other described methods for repairing tracheal injuries are primary repair without buttressing, and buttressing with gatric conduit serosal patch, graft and glue. In this study we reviewed different methods and outcome of repair described in the literature and our experienced of managing three cases.